2017
DOI: 10.1016/j.ijsu.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

The management of polyps in female reproductive organs

Abstract: Polyps of the lower reproductive tract are found in 7.8-50% of women. It has been hypothesized that cytogenetic modifications on chromosomes 6, 7 and 12 as well as epigenetic factors involving enzyme and metabolic activities may cause polyps to develop. Cervical polyps found in 2-5% of cases are of low clinical significance and can cause, although rarely, post coital bleedings. Cervical polyps grow during pregnancy and mucorrhoea. Trans vaginal ultrasound (TVU) provides an excellent diagnostic technique to dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 49 publications
0
49
0
7
Order By: Relevance
“…ПЭ занимают ведущее место в структуре внутриматочной патологии, но до настоящего момента многие звенья патогенеза данного заболевания остаются неизученными [1][2][3][4]. Поскольку CD34 является показателем микрососудистой плотности, его высокая экспрессия в ПЭ говорит о большем числе сосудов по сравнению с прилежащим и неизмененным эндометрием.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…ПЭ занимают ведущее место в структуре внутриматочной патологии, но до настоящего момента многие звенья патогенеза данного заболевания остаются неизученными [1][2][3][4]. Поскольку CD34 является показателем микрососудистой плотности, его высокая экспрессия в ПЭ говорит о большем числе сосудов по сравнению с прилежащим и неизмененным эндометрием.…”
Section: Discussionunclassified
“…Полипы эндометрия (ПЭ) являются одной из наиболее распространенных форм внутриматочной патологии и служат причиной аномальных маточных кровотечений (АМК) как в репродуктивном периоде, так и в менопаузе. Для них также характерна высокая частота рецидивов, приводящих к неоднократным оперативным вмешательствам, снижающим качество жизни женщин, повреждающим эндометрий и повышающим риск возникновения внутриматочных синехий и бесплодия [1][2][3][4]. Доля ПЭ, манифестирующихся АМК, в зависимости от методов диагностики и возрастных групп, колеблется от 38% до 81,5% [3,4].…”
Section: Introductionunclassified
See 2 more Smart Citations
“…ndometrial polyps are localized overgrowths of glands and stroma within the inner lining of the uterus. Cytogenetic modifications on chromosomes 6, 7, 12 and epigenetic factors involving enzyme and metabolic activities are suggested for the etiology (1). Endometrial polyps are more frequently observed in patients with endometriosis (2).…”
mentioning
confidence: 99%